Tissue engineering and cartilage - Kessler, Michael W (Landes Bioscience, 2008)
Human articular cartilage is an avascular structure, which, when injured, poses significant hurdles to repair strategies. Not only does the defect need to be repopulated with cells, but preferentially with hyaline-like cartilage. Successful tissue engineering relies on four specific criteria: cells, growth factors, scaffolds, and the mechanical environment. The cell population utilized may originate from cartilage itself (chondrocytes) or from growth factors that direct the development of mesenchymal stem cells toward a chondrogenic phenotype. These stem cells may originate from various mesenchymal tissues including bone marrow, synovium, adipose tissue, skeletal muscle, and periosteum. Another unique population of multipotent cells arises from Wharton's jelly in human umbilical cords. A number of growth factors have been associated with chondrogenic differentiation of stem cells and the maintenance of the chondrogenic phenotype by chondrocytes in vitro, including TGFβ; BMP-2, 4 and 7; IGF-1; and GDF-5. Scaffolds chosen for effective tissue engineering with respect to cartilage repair can be protein based (collagen, fibrin, and gelatin), carbohydrate based (hyaluronan, agarose, alginate, PLLA/PGA, and chitosan), or formed by hydrogels. Mechanical compression, fluid-induced shear stress, and hydrostatic pressure are aspects of mechanical loading found in within the human knee joint, both during gait and at rest. Utilizing these factors may assist in stimulating the development of more robust cells for implantation. Effective tissue engineering has the potential to improve the quality of life of millions of patients and delay future medical costs related to joint arthroplasty and associated procedures.